2013
DOI: 10.1561/100.00012033
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Gerrymandering: Political Geography and Electoral Bias in Legislatures

Abstract: While conventional wisdom holds that partisan bias in U.S. legislative elections results from intentional partisan and racial gerrymandering, we demonstrate that substantial bias can also emerge from patterns of human geography. We show that in many states, Democrats are inefficiently concentrated in large cities and smaller industrial agglomerations such that they can expect to win fewer than 50% of the seats when they win 50% of the votes. To measure this ''unintentional * The authors wish to thank

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
180
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(193 citation statements)
references
References 31 publications
7
180
0
6
Order By: Relevance
“…However, representative American democracy is also defined partly by its racial ideology, from In this study, we suggest that traditional debates over gerrymandering, analyzed as the process of drawing of boundaries around stable, residential populations (Chen and Rodden ,2013;Goedert 2014) Although four districts represent a small percentage of the state legislature, it means that over 100,000 black residents of Philadelphia do not experience representational equality as defined by the Supreme Court. While much research finds that incarceration has far reaching consequences on social and political life (see Wakefield and Uggen, 2010 for a review), we find that unequal political representation is a perhaps more insidious consequence of hyperincarceration that shifts political power away from urban people of color and toward rural, 28 predominantly white communities.…”
Section: Discussionmentioning
confidence: 89%
“…However, representative American democracy is also defined partly by its racial ideology, from In this study, we suggest that traditional debates over gerrymandering, analyzed as the process of drawing of boundaries around stable, residential populations (Chen and Rodden ,2013;Goedert 2014) Although four districts represent a small percentage of the state legislature, it means that over 100,000 black residents of Philadelphia do not experience representational equality as defined by the Supreme Court. While much research finds that incarceration has far reaching consequences on social and political life (see Wakefield and Uggen, 2010 for a review), we find that unequal political representation is a perhaps more insidious consequence of hyperincarceration that shifts political power away from urban people of color and toward rural, 28 predominantly white communities.…”
Section: Discussionmentioning
confidence: 89%
“…In the aftermath of the 2012 elections, a number of observers claimed that partisan redistricting was responsible for the disparity between House seats and vote shares, though this claim is controversial. Democrats, because of their high concentration in urban areas tend to be distributed less efficiently, thus giving Republicans a structural advantage (Chen & Rodden, 2013). Assigning causality to either mechanism is difficult and is not tested here, but it may offer a strong, and legitimate, justification for using commissions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, research arguing that partisan maps during the mild and predictable tides of the 1980s were very effective at creating bias (Owen andGrofman 1988, Cain 1985) countered studies showing little effect of partisan gerrymandering in 1970s, which featured big swings toward both parties (Squire 1985. With respect to nonpartisan commissions, Winburn (2004) and Hill (2008) find little effect of commissions on partisan bias, while Chen and Rodden (2013) find that neutral maps may in fact create unintended pro-Republican bias. Research has also shown the potential high responsiveness of partisan gerrymanders through backfires during adverse tides, but mostly though anecdotal examples of individual states and election years (e.g., Brunell 2005, Seabrook 2010).…”
Section: Goedertmentioning
confidence: 99%